Growth and nutrients competition between weedy rice and crop rice in a replacement series study - Ronnachit Jindalouang (2018)
© 2018 Friends Science Publishers. This study examined competitive ability of two rice varieties with a weedy rice biotype in pot experiment. In the first experiment, each of the rice variety was grown with the weedy rice in a replacement series experiment, with five proportions of crop to weedy rice at 100:0, 75:25, 50:50, 25:75 and 0:100. In the second experiment, cv. SPR1 crop rice and weedy rice were grown in monoculture and in 50:50 mixtures with mixed or separated roots. The weedy rice was more competitive than the two crop rice varieties, with proportionately greater number of tillers, grain yield, total dry weight and accumulation of nutrients in shoot of the weedy rice when grown at 75:25 crops to weed proportion. The competition between crop and weedy rice was predominantly in the roots, as the advantage of weedy rice in growth, yield and nutrients accumulation largely disappeared when the roots were separated. These results are in agreement with invasiveness of the weedy rice in crop field. The difference between crop rice varieties found here suggests that competitiveness against weedy rice could be selected for as part of the strategy for weedy rice control, with a focus on the root traits.